36-Nuclear anionic dimethylmalonate complexes of nickel(II) and cobalt(II) with cation of NBu4+: Synthesis, structure and magnetic properties. (7th July 2017) - Zorina-Tikhonova, Ekaterina N.; Gogoleva, Natalya V.; Sidorov, Aleksei A.; Aleksandrov, Grigory G.; Kiskin, Mikhail A.; Vologzhanina, Anna V.; Demina, Liudmila I.; Bogomyakov, Artem S.; Efimov, Nikolay N.; Mironov, Vladimir S.; Novotortsev, Vladimir M.; Eremenko, Igor L.
Graphical abstract: Here are the synthesis, structure and magnetic properties of 36-nuclear complexes of nickel(II) and cobalt(II) with anions of dimethylmalonic acid. Abstract: The reaction of (NBu4 )2 Me2 Mal (where Me2 Mal 2− is dimethylmalonate dianion) with cobalt(II) or nickel(II) acetates M(OAc)2 ·4H2 O (M = Co II or Ni II ) gave (NBu4 )6 [Co36 (H2 O-κO)12 (μ3 -OH)20 (μ4 -HMe2 Mal-κ 2 O, O′)2 (μ4 -Me2 Mal-κ 2 O, O′)22 (μ4 -Me2 Mal)6 ]·3EtOH (1 ) and (NBu4 )8 [Ni36 (H2 O-κO)12 (μ3 -OH)20 (μ4 -Me2 Mal-κ 2 O, O′)24 (μ4 -Me2 Mal)6 ]·6H2 O·2EtOH (2 ), respectively. Replacement of the aqueous NBu4 OH solution by a methanolic solution allowed us to isolate the 36-nuclear complex (NBu4 )8 [Co36 (H2 O-κO)12 (μ3 -OH)20 (μ4 -Me2 Mal-κ 2 O, O′)24 (μ4 -Me2 Mal)6 ]·2.5H2 O·CH3 OH (3 ). Complexes1 –3 were characterized by IR spectroscopy, single crystal X-ray diffraction analysis, and magnetochemical studies.